Molecularly Woven Cationic Covalent Organic Frameworks for Highly Selective Electrocatalytic Conversion of CO2 to CO - Fentahun Wondu Dagnaw; Karim Harrath; Tao Zheng; Xu‐Dong Wu; Yu‐Ze Liu; Rui‐Qi Li; Luo‐Han Xie; Zhen Li; Xuezhong He; Qing‐Xiao Tong; Jing‐Xin Jian (Advanced Science)
Abstract Coupling carbon capture with electrocatalytic carbon dioxide reduction (CO2R) to yield high‐value chemicals presents an appealing avenue for combating climate change, yet achieving highly selective electrocatalysts remains a significant challenge. Herein, two molecularly woven covalent organic frameworks (COFs) are designed, namely CuCOF and CuCOF+, with copper(I)‐bisphenanthroline complexes as building blocks. The metal–organic helical structure unit made the CuCOF and CuCOF+ present woven patterns, and their ordered pore structures and cationic properties enhanced their CO2 adsorption and good conductivity, which is confirmed by gas adsorption and electrochemical analysis. In the electrocatalytic CO2R measurements, CuCOF+ decorated with extra ethyl groups exhibit a main CO product with selectivity of 57.81%, outperforming the CuCOF with 42.92% CO at the same applied potential of 0.8 VRHE. After loading Pd nanoparticles, CuCOF‐Pd and CuCOF+‐Pd performed increased CO selectivity up to 84.97% and 95.45%, respectively. Combining the DFT theoretical calculations and experimental measurements, it is assumed that the molecularly woven cationic COF provides a catalytic microenvironment for CO2R and ensures efficient charge transfer from the electrode to the catalytic center, thereby achieving high electrocatalytic activity and selectivity. The present work significantly advances the practice of cationic COFs in real‐time CO2 capture and highly selective conversion to value‐added chemicals.